PENGARUH AIR REBUSAN DAUN HARENDONG BULU (Clidemia hirta) TERHADAP KADAR KOLESTROL MENCIT (Mus musculus) - Tuginah T; Dian Samitra; Eka Lokaria (LP4MK STKIP PGRI Lubuklinggau, 2020)
This study aims to determine the effect of giving boiled water leaves Clidemia hirta on the levels of male webster swiss mice cholesterol. This type of research is an experimental study using the Completely Randomized Design (CRD) method which consists of 5 treatments with 5 repetitions. The experimental animals in this study were male mice which were divided into 5 groups namely P0 (aquadest), P1 (MDLT + PTU + boiled water 0.13 ml/bb), P2 (MDLT + PTU + boiled water 0.26 ml/bb), P3 (MDLT + PTU + boiled water 0.39 ml/bb), and P4 (Simvastatin 10 mg). The treatment was carried out using the gavage method using a gastric sonde device, giving boiled bristle leaves boiled water in the morning for 7 consecutive days carried out in the morning. Retrieval of blood cholesterol levels data by cutting the tail of mice and the next drop blood on the cholesterol strip Autocheck tool. Based on the results of the Kruskal Wallis test calculation states that Hcount <Htable (4.626 <9.49), it can be concluded that the provision of boiled water leaves of Clidemia hirta does no effect significant in reducing levels of male Swiss Webster mice (Mus musculus) cholesterol levels.